Skin and nose. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
The cutaneous disorders involving the nose and its covering skin are affected by the peculiar characteristics of this region. First of all by the particular position of the nose, with its visibility and protrusion; moreover, by the characteristics of its skin, clinging to the underlying layers, scarcely liftable in folds and rich in sebaceous glands and finally by the continuity between the mucosa and the skin covering the nose level with the external nose orifices (...).